Evaluating effects of an exhibition visit on pre-service elementary teachers’ understandings of climate change - Sarıbaş, Deniz; Doğança Küçük, Zerrin; Ertepınar, Hamide (Journal of Turkish Science Education, 2016)
This research aims to investigate the extent to which a visit to a climate change exhibition embedded within an environmental education course affects pre-service elementary teachers’ understandings about climate change. The sample comprised 58 pre-service teachers, enrolled in the environmental education course offered as part of the Elementary Education program at a private university in Turkey during the 2011/2012 academic year. The course lasted 13 weeks and was composed of various environmental issues as well as an exhibition visit and student reflections. Pre- and post-reflections written by pre-service elementary teachers’ were analyzed and coded to examine the effect of the visit on their understanding of climate change. It was found that the course, and specifically the exhibition, had a positive effect on their understanding of climate change and ways in which to ameliorate the problem.